The effect of combination narrowband ultraviolet B phototherapy and vitamin D3 supplementation to increase serum 25-(OH)D levels in adult vitiligo patients - Reiva Farah Dwiyana; Fatima Aulia Khairani; Pusfana Meidelia; Unwati Sugiri; Reti Hindritiani; Hendra Gunawan; Oki Suwarsa (PAGEPress Publications, 2019)
Vitiligo is an acquired depigmentation disorder with exact etiology is not yet known. Autoimmune hypothesis plays an important role in the mechanism of vitiligo and has been related to lower levels of 25- hydroxyvitamin D (25-(OH)D). This study aimed to analyze the comparison effect of combination therapy of NB-UVB phototherapy and vitamin D3 supplement toward NB-UVB phototherapy alone to increase of serum 25-(OH)D levels in vitiligo patients. Subjects consisted of 24 adult vitiligo patients: group I was given a combination of NB-UVB phototherapy and 5000 IU vitamin D3 once daily; while group II was given monotherapy of NB-UVB. There was a very significant increase of serum 25- (OH)D level in group I with an average increase was 288.65%, while group II showed a significant increase of serum 25- (OH)D serum with an average increase was 33.63%. The very significant result was seen between both groups. None of the subjects showed signs of vitamin D toxicities during treatment. The study concluded that combination of NB-UVB phototherapy and vitamin D3 supplementation gave a better effect to increase of serum 25-(OH)D levels in adult vitiligo patients.